Pengaruh Digital Marketing dan Kualitas Produk Terhadap Keputusan Pembelian Toner Npure di Kota Surabaya - Winarsih, Siti; Yuliati, Nuriah; Fitriana, Nisa Hafi Idhoh (Universitas Galuh, 2024)
Purchasing decisions are an important aspect for companies in increasing sales of their products to consumers. This research aims to describe the reasons consumers make purchases online, as well as testing the influence of digital marketing and product quality on purchasing decisions for Npure Toner in the city of Surabaya. The sample determination method was purposive sampling with a total of 95 consumers ass respondents. The technique used ini collecting data is by distributing questionnaires. The first objective was analyzed descriptively qualitatively, the second objective used the SEM PLS 4.1 program to calculate and analyzed the data. The research result show that 1) Online purchase are more effective for Npure Toner consumers in the city of Surabaya in terms of benefits, price, trust, and ease of purchase. 2) Digital marketing dan product quality have a significant and positive influence on purchasing decision.